2021
DOI: 10.1542/peds.2020-016006
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Age and Weight for Very Preterm Infants: 2005–2018

Abstract: BACKGROUND: A complex set of medical, social, and financial factors underlie decisions to discharge very preterm infants. As care practices change, whether postmenstrual age and weight at discharge have changed is unknown. METHODS: Between 2005 and 2018, 824 US Vermont Oxford Network member hospitals reported 314 811 infants 24 to 29 weeks’ gestational age at birth without major congenital abnormalities who survived to discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…It has been reported that variation in the diagnosis and management of AOP and use of continuous pulse oximetry (CPO) contribute to inter-NICU variation in PMA at discharge. 2,3 We believe that the same variables might also explain much of the temporal trend in PMA at discharge reported by Edwards et al 1 In regard to AOP management, practices have been standardized in many NICUs such that the variation in duration of discharge countdowns reported in the 1990s and early 2000s has likely decreased, with countdowns of ,5 days more likely to be deemed inadequate. 4,5 In regard to diagnosis, it may be that increasing the use of CPO as a component of routine cardiorespiratory monitoring resulted in slower resolution of AOP.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…It has been reported that variation in the diagnosis and management of AOP and use of continuous pulse oximetry (CPO) contribute to inter-NICU variation in PMA at discharge. 2,3 We believe that the same variables might also explain much of the temporal trend in PMA at discharge reported by Edwards et al 1 In regard to AOP management, practices have been standardized in many NICUs such that the variation in duration of discharge countdowns reported in the 1990s and early 2000s has likely decreased, with countdowns of ,5 days more likely to be deemed inadequate. 4,5 In regard to diagnosis, it may be that increasing the use of CPO as a component of routine cardiorespiratory monitoring resulted in slower resolution of AOP.…”
mentioning
confidence: 79%
“…In this issue of Pediatrics, Edwards et al 1 present convincing evidence that the postmenstrual age (PMA), weight, and weight z score at discharge for preterm newborns increased between 2005 and 2018. It would be reasonable to speculate that the longer length of stay (LOS) might be attributed to rising survival rates and increasingly fragile survivors.…”
mentioning
confidence: 99%
“…Recent reports of changes in LOHS from the USA show an increasing trend in PAD from 2005 to 2018 for infants born at 24- to 29 weeks’ gestation. The authors suspect financial incentives as part of the cause of this development [5], as longer stay translates into increased remuneration in the USA. In contrast, a diagnose-related group system was introduced in Germany intended to curb the spending on hospitals in 2000.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of increased rates of survival in preterm infants with very low birth weight (<1,500 g, VLBW) [1, 2] on LOHS and postmenstrual age at discharge (PAD) has rarely been investigated. LOHS of VLBW infants is not only influenced by biological factors and medical treatment [3, 4] but possibly also by financial incentives [5]. A recent study from the USA revealed in an overall increase in weight and PAD over the last decade [5] in spite decreased LOHS and PAD in infants born at less than 28-week gestation from 1993 to 2021 (42 vs. 37 weeks) [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation